The Influence of Corporate Social Responsibility on Corporate Image (PT Industri Jamu dan Farmasi Sido Muncul Tbk, Bergas Kidul) - Retno, Martha Vella Ayu; Widyasari, Suzy (Manunggal Halim Jaya, 2026)
This study aims to examine the impact of Corporate Social Responsibility (CSR) on the corporate image of PT Industri Jamu dan Farmasi Sido Muncul Tbk., focusing on social, economic, and environmental dimensions. A positive corporate image is considered a strategic asset, and CSR serves as a key approach to achieve it. Employing a quantitative method, the study surveyed 100 purposively selected respondents from Bergas Kidul, the community surrounding the company, who had directly benefited from its CSR initiatives. Data were collected via questionnaires and analyzed using multiple linear regression. The findings indicate that the social and environmental aspects of CSR have a significant and positive influence on corporate image, whereas the economic aspect shows no significant impact. The study concludes that CSR programs emphasizing social welfare and environmental sustainability effectively enhance the corporate image of PT Industri Jamu dan Farmasi Sido Muncul Tbk within the Bergas Kidul community.